Social Perception of Self-Enhanced Photographs - Parsa, Keon M.; Charipova, Karina; Chu, Eugenia; Reilly, Michael J. (Facial Plastic Surgery, 2021)
The use of appearance manipulating applications on our smartphones has increased in popularity. As the aim of this study is to determine the impact of self-directed appearance manipulation on perceptions of personality and examine the influence of respondent age and gender on the various personality domains. This cross-sectional cohort study included 20 subjects between the ages of 18 to 34 who had headshots taken and were provided an introduction on the use of the Facetune2 app. After 1 week of engaging in digital appearance manipulation, subjects submitted their self-determined most attractive edited photograph. Four surveys were constructed with 10 sets of photographs each. Each of these surveys were then sent to lay people via a web-based survey tool. Anonymous blinded respondents used a 7-point Likert scale to rate their perception of each patient's aggressiveness, likeability, sociability, trustworthiness, attractiveness, authenticity, and masculinity or femininity. A multivariate linear mixed effect model was applied to analyze the overall patient trait data as well as to assess the impact of rater age and gender. A total of 288 respondents (mean age range, 25–34 years [43%]; 202 [70%] female) completed a survey. Overall, digitally enhanced photographs were perceived as more attractive (0.22; 95% CI, 0.06–0.38). Analysis based on gender of the study subjects revealed increased attractiveness scores for men (0.19; 95% CI, 0.07–0.33). Females were also perceived as being more attractive (0.16; 95% CI, 0.03–0.40), but less authentic (−0.24; 95% CI, −0.36 to −0.12). Females rated enhanced photographs of men as less masculine (−0.23; 95% CI, −0.46 to −0.04). Raters aged 35 to 64 rated altered photos as less attractive (0.31; 95% CI, 0.09–0.52), authentic (0.20; 95% CI, 0.01–0.38), and gender enhancing (0.42; 95% CI, 0.24–0.61) compared with individuals aged 18 to 34. Patients and surgeons should be aware of the ways in which self-enhanced photographs may affect social perception.
Keywords: selfie; Facetune; attractiveness; authenticity; appearance manipulation